Trends in Knowledge Organization Processes and Systems for fictional narrative texts - Lima, Larissa de Mello [UNESP]; Almeida, Patricia de; Ernesto de Moraes, Joao Batista [UNESP]; Martinez-Avila, Daniel; Caprioli, Mariana da Silva [UNESP]; Vaz Tenorio, Luana Calcete [UNESP] (Univ Zaragoza, 2020)
We analyze the latest publications on fiction knowledge organization, retrieved from the ISKO database Knowledge Organization Literature, aiming to outline the current situation of the area as well as to identify trends. We used Hjorland's categories of Knowledge Organization Processes and Knowledge Organization Systems for the analysis. We extracted textual discursive units from each text to support their categorization. We conclude that since 2010 the trend is to work on knowledge organization processes of fiction as even those publications that dealt with fiction knowledge organization systems also discussed the processes.
Keywords: Fiction; Knowledge Organization Processes; Knowledge Organization Systems